The Role of Wood Ants (Formica rufa group) in Carbon and Nutrient Dynamics of a Boreal Norway Spruce Forest Ecosystem - Leena Finér; Martin F. Jurgensen; Timo Domisch; Jouni Kilpeläinen; Seppo Neuvonen; Pekka Punttila; Anita C. Risch; Mizue Ohashi; Pekka Niemelä (Ecosystems, 2013)

Genetic and Environmental Factors Behind Foliar Chemistry of the Mature Mountain Birch - Sanna Haviola; Seppo Neuvonen; Markus J. Rantala; Kari Saikkonen; Juha-Pekka Salminen; Irma Saloniemi; Shiyong Yang; Teija Ruuhola (Journal of Chemical Ecology, 2012)

Extensive tree health monitoring networks are useful in revealing the impacts of widespread biotic damage in boreal forests - Seppo Nevalainen; Martti Lindgren; Antti Pouttu; Jaakko Heinonen; Marke Hongisto; Seppo Neuvonen (Environmental Monitoring and Assessment, 2010)

The Significance of Ectomycorrhizas in Chemical Quality of Silver Birch Foliage and Above-Ground Insect Herbivore Performance - Anne-Marja Nerg; Anne Kasurinen; Toini Holopainen; Riitta Julkunen-Tiitto; Seppo Neuvonen; Jarmo K. Holopainen (Journal of Chemical Ecology, 2008)

The role of competitors for Chrysomela lapponica, a north Eurasian willow pest, in pioneering a new host plant - Jürgen Gross; Nina E. Fatouros; Seppo Neuvonen; Monika Hilker (Journal of Pest Science, 2007)

Reduction in size and fecundity of the autumnal moth, Epirrita autumnata, in the increase phase of a population cycle - Tero Klemola; Kai Ruohomäki; Tommi Andersson; Seppo Neuvonen (Oecologia, 2004)

Micro‐fungi and invertebrate herbivores on birch trees: fungal mediated plant–herbivore interactions or responses to host quality? - Jouni Ahlholm; Marjo Helander; Pirjo Elamo; Irma Saloniemi; Seppo Neuvonen; Sinikka Hanhimäki; Kari Saikkonen (Ecology Letters, 2002)
We studied interactions between microfungi and herbivores sharing a host tree. In a series of experiments and field observations over a 3‐year period, we compared phenotypic and genetic correlations of fungal frequencies and performance of invertebrate herbivores growing on mature half‐sib progenies of mountain birches ( Betula pubescens ssp. czerepanovii ) in two environments, a forested river valley and an adjacent higher‐elevation mountain birch woodland. We found little support for direct relation between fungal frequencies and performance of herbivore species. Instead, genetic correlations, particularly between autumnal moth ( Epirrita autumnata ) and rust fungus ( Melampsoridium betulinum ), suggest that herbivore performance may be caused by (1) genetic differences in plant quality for fungi and herbivores, or (2) genetic differences in responses to environmental conditions.

The influence of hybridization on epidermal properties of birch species and the consequences for palaeoclimatic interpretations - Friederike Wagner; Seppo Neuvonen; Wolfram M. Kürschner; Henk Visscher (Plant Ecology, 2000)

Performance of moth larvae on birch in relation to altitude, climate, host quality and parasitoids - Tarmo Virtanen; Seppo Neuvonen (Oecologia, 1999)

Birch family and environmental conditions affect endophytic fungi in leaves - Pirjo Elamo; Marjo L. Helander; Irma Saloniemi; Seppo Neuvonen (Oecologia, 1999)

Wood ants and a geometrid defoliator of birch: predation outweighs beneficial effects through the host plant - Kari J. Karhu; Seppo Neuvonen (Oecologia, 1998)

Species richness of vascular plantsin the subarctic landscape of northern Finland:modelling relationships to the environment - RISTO K. HEIKKINEN; SEPPO NEUVONEN (Biodiversity and Conservation, 1997)